Evaluation of Henry Constant for Gas / Gas Mixture in Pure and Solvent Mixture Using Simple Functional Mixing Rule. Issue 1 (February 2021) - Lai, A J X; Basha, A N; Tan, L S; Tsuji, T; Hoshina, T; Funazukuri, T; Bharath, R
Abstract: Some mixing rules were proposed with simple functional form to predict binary gas mixture solubility in pure solvent/pure gas solubility in binary solvent mixture. The experimental data employed were those of Tsuji et al. (2019) for equimolar binary gas mixture (nitrogen (N2) + oxygen (O2)) solubility in styrene at 303 K, and of Tsuji et al. (2005) for hydrogen (H2) solubility in equimolar mixture of benzene + cyclohexane at 303 K. These solubilities have a linear pressure dependence like Henry's law at least up to 4.827 MPa. To predict gas solubilities, the mixing rules were proposed for Henry constant of gas mixtures in pure solvent and that of pure gas in solvent mixture just by using Henry constant of pure gas in pure solvent without any binary parameter. The function form was similar to that of van der Waals one fluid model, Q = ∑i ∑j zi zj Q ij for the mole ratio of constituent of gas or solvent mixture, zi . The Q = H and Q ij = ( H i + H j )/2 show the best reproducibility for (N2 + O2) solubility in styrene with average absolute relative deviation (AARD) 0.667 %. Otherwise, the Q = 1/H and Q ij = (1/ H i + 1/ H j )/2 show the best reproducibility for H2 solubility in benzene + cyclohexane with AARD 5.605 %. The results were well described by a universality of physical properties and Lorentz-Berthelot theorem.